Characterization of Formononetin Sulfonation in SULT1A3 Overexpressing HKE293 Cells: Involvement of Multidrug Resistance-Associated Protein 4 in Excretion of Sulfate - Liu, Fanye; Pei, Shuhua; Li, Wenqi; Wang, Xiao; Liang, Chao; Yang, Ruohan; Zhang, Zhansheng; Yao, Xin; Fang, Dong; Xie, Songqiang; Sun, Hua (Frontiers in Pharmacology, 2021)
Formononetin is one of the main active compounds of traditional Chinese herbal medicine Astragalus membranaceus. However, disposition of formononetin via sulfonation pathway remain undefined. Here, expression-activity correlation was performed to identify the contributing of SULT1A3 to formononetin metabolism. Then the sulfonation of formononetin and excretion of its sulfate were investigated in SULT1A3 overexpressed human embryonic kidney 293 cells (or HKE-SULT1A3 cells) with significant expression of Breast Cancer Resistance Protein (BCRP) and Multidrug Resistance-associated Proteins 4 (MRP4). As results, formononetin sulfonation was significantly correlated with SULT1A3 protein levels (r = 0.728; p < 0.05) in a bank of individual human intestine S9 fractions (n = 9). HEK-SULT1A3 cells catalyzed formononetin formed a mono-sulfate metabolite. Sulfate formation of formononetin in HEK-SULT1A3 cell lysate followed the Michaelis-Menten kinetics (Vmax = 13.94 pmol/min/mg and Km = 6.17 μM). Reduced activity of MRP4 by MK-571 caused significantly decrease in the excretion rate (79.1% - 94.6%) and efflux clearance (85.3% - 98.0%) of formononetin sulfate, whereas the BCRP specific inhibitor Ko143 had no effect. Furthermore, silencing of MRP4 led to obvious decrease in sulfate excretion rates (>32.8%) and efflux clearance (>50.6%). It was worth noting that the fraction of dose metabolized (fmet), an indicator of the extent of drug sulfonation, was also decreased (maximal 26.7%) with the knockdown of MRP4. In conclusion, SULT1A3 was of great significance in determining sulfonation of formononetin. HEK-SULT1A3 cells catalyzed formononetin formed a mono-sulfate. MRP4 mainly contributed to cellular excretion of formononetin sulfate, and further mediated the intracellular sulfonation of formononetin.